Studi kasus bank islam Al-Tadamon di Sudan: Pengaruh informasi yang dihasilkan terhadap efisiensi bank: Strategi perencanaan sebagai mediator - Aprilia, Fania (Maliki Interdisciplinary Journal, 2025)
This study uses strategic planning as a mediating variable to test how the knowledge generated affects bank efficiency. mediating variable to test how the knowledge generated affects bank efficiency. One of the leading Islamic financial organizations in Sudan, became the research location. Bank employees and management were given questionnaires as part of a quantitative research strategy. questionnaires as part of a quantitative research strategy. Regression and mediation tests were used to analyze the data to see the correlation between the research variables. The findings show that the information generated significantly and positively affects bank efficiency and relevant information helps improve the effectiveness of strategic planning. A partial mediator between generated information and bank efficiency, strategic planning was also found to have a favorable effect on bank efficiency. These results demonstrate that improving performance and operational efficiency in Islamic banking requires well considered strategic planning and information management. The report offers useful advice on how bank management can improve internal information systems and use them into strategic planning to gain a long-term competitive edge.